SOME RELATIONSHIPS BETWEEN INDIAN AND STOIC LOGIC. - López-Astorga, Miguel (Problems / Problemos, 2016)
In this paper, I try to show that Indian and Stoic logic are more similar to each other than to standard logic. To do that, I analyze a passage of the Kathāvatthu that has been interpreted as proposing the definition of the conditional assumed by modern propositional logic, and argue that that interpretation is not absolutely justified. In this way, I contend that what is said in that passage and the actual view of the conditional presented in the Kathāvatthu are also consistent with the criterion of the conditional held by Chrysippus of Soli.